Obstetric Anesthesia Handbook Fifth Edition - Datta, Sanjay; Kodali, Bhavani Shankar; Segal, Scott; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
For nearly two decades, anesthesiologists and obstetricians have turned to this handbook as the definitive reference for obstetric anesthesia. Authoritative yet concise, it has been designed as a practical guide to all aspects of anesthesia for childbirth and related obstetric procedures, including perinatal pharmacology, relief of labor pain, fetal monitoring, anesthesia for cesarean delivery, high risk pregnancy, and in vitro fertilization. The fifth edition of Obstetric Anesthesia Handbook has been reorganized and revised to both update the content and help expedite the retrieval of the most pertinent information. New chapters include "Pain of Labor and Delivery" and "Effects of Epidural Analgesia on Labor and the Infant." An appendix has been added that includes the most recent national guidelines for obstetric anesthesia. With numerous illustrations and tables, as well as updates regarding new medications and techniques, this esteemed handbook is more valuable than ever.
Maternal Physiological Changes During Pregnancy, Labor, and the Postpartum Period -- Local Anesthetic Pharmacology -- Perinatal Pharmacology -- Drug Interactions and Obstetric Anesthesia -- Uteroplacental Blood Flow -- Pain of Labor and Delivery -- Non-pharmacological Methods for Relief of Labor Pain -- Relief of Labor Pain by Systemic Medications and Inhalational Agents -- Relief of Labor Pain by Regional Analgesia/Anesthesia -- Effects of Epidural Analgesia on Labor and the Infant -- Fetal Monitoring -- Anesthesia for Cesarean Delivery -- Neonatal Resuscitation -- High-Risk Pregnancy: Maternal Comorbidity -- High-Risk Pregnancy: Pregnancy-Related Problems -- Non-delivery Obstetric Procedures -- Anesthesia for Nonobstetric Surgery During Pregnancy -- Assisted Reproductive Technology -- Maternal Mortality and Morbidity.
Keywords: Medicine; Anesthesiology; Obstetrics; Medicine & Public Health; Anesthesiology; Obstetrics/Perinatology.